Dental Biopolymer Composites with Antibiotics, Bisphosphonate, and Hydroxyapatite for Possible Use in Bone Tissue Regeneration - Mihaela Maria Budiul; Gabriela Vlase; Daniel Negru; Dorinel Okolišan; Ionela-Amalia Bradu; Alexandra Tăşală; Alexandru Pahomi; Titus Vlase; Daniela Jumanca; Atena Galuscan; Paula Sfirloaga; Nicoleta Carabă; et al. (Journal of Chemistry)
The aim of the present study was to formulate new variants of synthetic and animal-source bone materials coated with different biopolymers, containing antibiotics (ampicillin and oxacillin) and alendronate drugs. Validation consists in establishing mixtures that do not present interactions between components. These materials should act as a drug delivery system alongside the bone base. Natural polymers such as chitosan, alginate, and kappa-carrageenan have been shown to be optimal materials for drug delivery due to their intrinsic biocompatibility. Binary, ternary, and quaternary mixtures between components are analyzed by FT-IR spectroscopy, UV-Vis analysis, thermogravimetry (TGA), and scanning electron microscopy (SEM). The analysis led to the validation of materials suitable for the controlled release of active substances, which have the greatest chance of increasing the speed of bone regeneration, as well as helping in the local administration of antibiotics, which currently must be administered in the form of oral formulations or an injection. According to the FTIR, thermogravimetry, UV-Vis, SEM, and cytotoxicity tests performed in this study, it can be said that it is quite easy to obtain materials that can be used in dental practice that facilitate bone reconstruction through local treatment. At the same time, it was found that both active substances can be incorporated into the material together with Alg and Chit, thus limiting the adverse effects and maximizing the local beneficial effects.